ADAPTIVE THERMAL COMFORT ON SAO PU’U TRADITIONAL HOUSE IN WOGO VILLAGE, EAST NUSA TENGGARA - I Ketut Suwantara; Rini Nugrahaeni; Iwan Suprijanto (Widyariset, 2012)
Indonesia has two seasons, rainy and dry season which affects the adaptive behavior of the occupants. One of the traditional houses that still survive is a traditional house Sao Pu’u in Wogo village, East Nusa Tenggara. The research was conducted to compare of neutrality, preferences, and thermal acceptance of the occupants in the house between rainy and dry season. Thermal value was measured with Questem 34 and wind velocity measured with Anemometre Kanomax. The data were processed using regression analysis. In the rainy season, neutral temperature, 27.1oC, 23.9°C,and 23.3°C. Meanwhile, in the dry season, neutral temperature, preference temperature, and thermal acceptance were 24,9oC, 23.4°C, and 27.1oC. The conclusion was that the occupants prefer a lower temperature adaptively both in rainy and dry season.